Paul and Barnabas in Lystra (Acts 14:8-20): the contextualization of the Gospel in a Graeco-Roman city - Germiquet, Edouard Ariste (Rhodes University, Faculty of Divinity, Department of Divinity, 1992)
This thesis will investigate the extensive Graeco-Roman characteristics of the Lystra speech and in so doing convey some clarity in the otherwise widely differing opinions held about it. This will be achieved by showing that Lystra was a Hellenistic city of some importance with a varied population. It will be argued that the initial reaction of the Lystrians to the miraculous healing of the cripple is to be understood as representing typical Graeco-Roman notions. This will include Luke's use of a legend which not only adds local colouring to the narrative but also introduces Graeco-Roman themes such as the blurring of the distinction between humans and gods and the custom of sacrifice. This contextualization immediately portrays the Graeco-Roman nature of the Lystrians' behaviour and attitudes. In addition to these themes it will be argued that the Lystrians are shown to being reliant on secondary notions of God, which when exposed to the proclamation of the apostles will prove to be inadequate. It will also be argued that the speech of the apostles is structured in a typically Graeco-Roman rhetorical form, where the errors are first exposed before the truth is presented. In conjunction with this structure it will be argued that the philosophical concept of which Dibelius has shown to be clearly presupposed in the Areopagus speech, is not only present in the Lystra speech but forms the philosophical basis on which it is structured. This concept explains the insistence by the apostles that they are human and that God has no need of such worthless things as sacrifices. It also explains the presentation of God's activity in creation and providence as an antithesis to a god who is in need. The Graeco-Roman aspects are brought to a close with the discussion of idea that an awareness of God does not depend on secondary notions acquired from legends or customs but that the truth is grasped through a process of reflection on creation and providence. This is an important notion in the speech for it exposes the Lystrians as being in need of a reorientation of their beliefs in God, away from those which are secondary to those which are primary and compatible with the truth.
Keywords: Bible. Acts -- Criticism, interpretation, etc.